Indonesian Employment and Labor Policy: A Pancasila Perspective - Syuhada, Otong; Razali, Rodziana Mohamed (Kosmik Hukum, 2024)
The aim of this research is to examine and analyze how the Pancasila legal state concept treats labor as the most important part of the national development process. The existence of workers in the national development process has a strategic and decisive position; without workers, it is impossible for a development plan to be implemented well. In Employment Law No. 13 of 2003, workers are placed as actors of development as well as development goals. The meaning of this sentence is that workers are not only involved in the development process but also as parties who are obliged to enjoy the results of development. The method used in this research is sociological juridical with a legal approach and a conceptual approach, while the data used is secondary data, which includes material. primary legal materials, secondary legal materials, and tertiary legal materials. From the research results, it was found that there is a gap in the implementation between the concept of the Pancasila rule of law and the reality that occurs in the world of work. The rights of workers as human beings are often neglected. It is difficult for workers to achieve a prosperous life because the wages they receive cannot meet the needs of a decent life, so the concept of just and civilized humanity has not been achieved by workers. Based on these conditions, researchers recommend that the government immediately take concrete steps to overcome the problem of disparities in workforce welfare.Keywords: Employment, Labor Policy; Pancasila